Students’ Personnel Services for bridging the gaps between Schooling and Employability of Nigerian Polytechnic Graduates - Ogundele, Michael Olarewaju; Chalibiya, Simon; Sabo, Muhammad Adamu; Oparinde, Yemi (NIU Journal of Social Sciences, 2018)
The paper examined students’ personnel services that are available for bridging the gap between schooling and employability of Nigerian Polytechnic graduates. The issues relating to the concepts and types of students personnel services are looked into. The paper however examined application of the personnel services for bridging the gaps between schooling and employability of Nigerian polytechnic graduates the mode of operation and relevance to polytechnic students’ needs while in schools and be used when they graduates, that will make them be graduates that will be job creators, employers of labour and reducing poverty and unemployment in the Country. It was however suggested that effective use of information, career, psycho-social, guidance and counseling services will aid Nigerian polytechnic students to bridge the gaps between schooling and employability after graduation. Keywords: students’ personnel services, schooling, employability, and polytechnic graduates